I who have never known men / Jacqueline Harpman ; translated by Ros Schwartz. - Harpman, Jacqueline (Vintage editions., 2019)
Deep underground, 39 women live imprisoned in a cage. Watched over by guards, the women have no memory of how they got there and only vague notions of their lives before. As the burn of electric light merges day into night and numberless years pass, a young girl - the fortieth prisoner - sits alone and outcast in the corner. But soon she will show herself to be the key to the others' escape and survival in the strange world that awaits them above.